Assessment of the Microbiological Quality and Safety in Takeaway Sushi Meals in Portugal - Sandy J.C. Alegria; Maria Isabel S. Santos; Rosália M.S. Furtado; Cristina Belo Correia; Ana Isabel G. Lima; Laurentina R. Pedroso; Sónia Catarina da Silva Ramos (Karger Publishers, 2022)
Being a food product that contains perishable ingredients and involves a significant degree of manual handling during preparation, sushi is regarded as a potentially hazardous food, which may lead to foodborne disease outbreaks. In Portugal, consumption of takeaway sushi meals has strongly increased throughout the past few years; however, there is limited information regarding its compliance with food quality standards. Under this context, the present study aimed to evaluate the microbiological quality and safety of take-away ready-to-eat sushi meals in Lisbon, Portugal. Sixty-two samples were collected from different origins (restaurant and hypermarket), and each sample was tested for aerobic mesophilic microorganisms, Enterobacteriaceae, Escherichia coli, positive coagulase Staphylococci, presumptive Bacillus cereus count, as for detection of pathogenic microorganisms, such as Salmonella spp., Listeria monocytogenes and Vibrio parahaemolyticus, V. cholerae and V. vulnificus. Results revealed that 48.4% (30/62) were deemed unsatisfactory, 35.5% (22/62) were classified as borderline and only 16.1% (10/62) were considered satisfactory. Even though we did not detect the incidence of potentially pathogenic microorganisms in sushi, the presence of B. cereus and coagulase-positive Staphylococci was detected at unsatisfactory levels. Furthermore, significant differences between the place of origin (restaurant vs. hypermarket) and type of fish were also observed. Overall, the high number of samples classified with a level of microbiological quality "unsatisfactory" and "borderline" highlights the need to review good hygiene practices, as well as the quality of the raw materials used, to obtain a final product with a satisfactory quality and safety level.